Barriers to international capital flows: who should erect them and how big should they be? - Marco A. Espinosa-Vega; Bruce D. Smith; Chong K. Yip (Federal Reserve Bank of Atlanta, 1999)
Until recently, the trend in world capital markets has been toward increasing globalization. Recent events in Latin America and Asia have caused many in policy-making circles to question whether this trend should be wholly, or at least partially, reversed. It is commonly argued that—at a minimum—countries should be given the discretion to erect such barriers, at least in certain circumstances. Recent events, then, have forced a rethinking of the desirability of unrestricted world capital flows. The general presumption appears to be that the "victims" of highly volatile capital flows should be allowed to limit or restrict inflows and outflows of funds. But outflows of funds from smaller and less developed economies often represent inflows of funds to larger and more developed economies. This raises the issue of whether there would be benefits associated with larger and wealthier economies taking actions to limit capital mobility. This paper presents a formal analysis of erecting barriers to international capital flows. We find that, in contrast to conventional thinking, when there are substantial differences in per capita GDP across countries, long-run output in all countries can be increased by having wealthier economies erect some partial barriers to capital mobility. Interestingly, wealthier economies need not persuade poorer economies to cooperate: by implementing an appropriately selected tax on capital flows it will often be the case that the wealthy economy can unilaterally obtain a higher steady state welfare level for all agents in all economies. We also show that these same barriers need not eliminate endogenously arising volatility in income, capital flows, and asset returns. Under some circumstances, then, if it is desirable to reduce such volatility, this must be accomplished by other means. However, and this bears emphasis, the case for imposing barriers on capital flows does not depend critically on the ability of these barriers to eliminate excess volatility.
Keywords: 330; Capital market; Capital movements; International economic relations